An examination on rewards, recognition, and ownership vis-a-vis corporate entrepreneurship in Singapore - Chionh, Hai Guan (2009)
The importance of corporate entrepreneurship has been given increasing recognition in the last decade or more. This recognition has developed parallel to the acknowledgment of the vital roles that individual innovation; ingenuity and initiative play in the corporate growth and competitiveness in a rapid changing business environment. Based on the notion of creating wealth and adding value in light of the definition given by Kao (1993), an organization can create an environment in which all of its members can contribute in one way or other to the entrepreneurial function.